Police militarization understanding the perspectives of police chiefs, administrators, and tactical officers - Phillips, Scott W. (Routledge innovations in policing, 2018)
The increased militarization of the police in the United States has been a topic of controversy for decades, brought to the public eye in notable events such as the Los Angeles Police Department's use of battering rams in the 1980s and the siege of the Weaver family at Ruby Ridge, Idaho, in the 1990s, among others. These themes are explored in detail, suggesting multiple dimensions, both theoretical and empirical, to better understand policing and policy, making this book an excellent resource for students, scholars, and professionals in law enforcement, political science, and public administration.